RST invariant watermarking technique for vector map based on LCA-transform - Saleh AL-ardhi; Vijey Thayananthan; Abdullah Basuhail (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
The dangers of copyright protection can impact 2D vector maps, having a knock-on effect on the use of vector data. To achieve invariance property, uniform RST (rotation, scaling and translation) and disguising the digital vector map’s information by implementing distortion control, is all done by using watermarking schemes. Convert an original map, then engrain the watermark. An LCA algorithm is used in this study, as a newly proposed way to protect the vector maps under copyright. The procedure is operated in this order: 1) use an original map, altered by the LCA algorithm, 2) use the coefficient of the transformation to engrain the watermark, inserting the resulting frequency into the LSB wave, 3) the watermarked map is acquired by using the inverse LCA map transformation. Further investigations discovered that the necessary standards of fidelity and invisibility can be achieved using this technique. This procedure also gives out numerous frequency domains for digital watermarking; as well as being resilient to signal and geometric invasions.